A three dimensional free body analysis describing variation in the musculoskeletal configuration of the cynodont lower jaw. Issue 1 (13th January 2016) - Reed, D. A.; Iriarte‐Diaz, J.; Diekwisch, T. G. H.
Summary: The evolution of the middle ear from the cynodont craniomandibular bones is one of the key mammalian innovations, and the mechanics underlying this anatomical transformation represents an intriguing paradox. Because the jaw joint of nonmammalian cynodonts was functionally coupled to the inner ear, auditory performance would favor low joint reaction forces. However, this could not be achieved at the expense of feeding performance, favoring high bite forces. The balance of these two seemingly incompatible performance criteria in the context of the morphological diversity of the cynodont lower jaw is poorly understood. Here we derive a series of equations using three dimensional free body analysis that describe the relationship between the orientation and position of the jaw elevator muscles, the position of the jaw articulation relative to the bite point, the joint reaction forces and the bite force in the lower jaw of the nonmammalian cynodont Probainognathus . These equations permit the effects of variation in each variable to be tested independently, yielding three terms that act to limit joint reaction forces without substantially impacting bite force: the reorientation of the resultant muscle force more vertically, shifting the position of the bite point medial to the jaw articulation, and elevating the jaw articulation above the level with the tooth row only when the muscles are oriented principally in the anterior direction. The predictions from our equations provide insights for functional interpretations of patterns of morphological diversity in the cynodont fossil record. They also illustrate that the musculoskeletal configuration of the cynodont lower jaw can be evolutionarily labile without negatively impacting the dual performance criteria of the auditory and feeding system.